2021
DOI: 10.1523/jneurosci.3102-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Epigenetic Modifiers LSD1 and HDAC1 Blocks Rod Photoreceptor Death in Mouse Models of Retinitis Pigmentosa

Abstract: Epigenetic modifiers are increasingly being investigated as potential therapeutics to modify and overcome disease phenotypes. Diseases of the nervous system present a particular problem as neurons are postmitotic and demonstrate relatively stable gene expression patterns and chromatin organization. We have explored the ability of epigenetic modifiers to prevent degeneration of rod photoreceptors in a mouse model of retinitis pigmentosa (RP), using rd10 mice of both sexes. The histone modification eraser enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…Indeed, a previous study in the rd1 model of RP showed upregulation of the repressive methylation site H3K27me3 in rods whereby inhibition of histone methylation delayed rod degeneration [19]. Similarly, inhibition of lysine demethylase 1, which specifically demethylates H3K4me1/2 and H3K9me1/2, blocks rod degeneration in rd10 mice [20]. Contrary to rods, our study shows that wt cones have high levels of H3K27me3, which is diminished in degenerating Pde6c mutant cones.…”
Section: Pde6c Cpfl1 Cones Have Reduced Expression Of H3k27me3 Which ...supporting
confidence: 56%
See 2 more Smart Citations
“…Indeed, a previous study in the rd1 model of RP showed upregulation of the repressive methylation site H3K27me3 in rods whereby inhibition of histone methylation delayed rod degeneration [19]. Similarly, inhibition of lysine demethylase 1, which specifically demethylates H3K4me1/2 and H3K9me1/2, blocks rod degeneration in rd10 mice [20]. Contrary to rods, our study shows that wt cones have high levels of H3K27me3, which is diminished in degenerating Pde6c mutant cones.…”
Section: Pde6c Cpfl1 Cones Have Reduced Expression Of H3k27me3 Which ...supporting
confidence: 56%
“…GSK-J4 was initially developed as a selective inhibitor of the H3K27me2/3 demethylases Kdm6a and Kdm6b but was later found to inhibit multiple members of the Jumonji-C domain-containing family, including the Kdm5 subfamily, which is responsible for the demethylation of active H3K4me1/2/3 markers [50]. As the methylation state of both H3K4 and H3K27 can be protective in neurodegeneration [20, 51], it indicates a role for GSK-J4 in concomitantly inhibiting both Kdm6 and Kdm5 subfamilies and suggest its neuroprotective action may involve the activity of both repressive H3K27me and active H3K4me.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned, LSD1 has been reported to suppress H3K4me1 modification to suppress neurogenesis and impair hippocampal memory in mice (Zhang et al., 2021 ). LSD1 inhibition showed neuroprotective activity, and one of the major pathways was targeting histone modifications and restoration of the neuroprotective genes and cascades, including the Wnt pathway (Popova et al., 2021 ). Of note, in the present study, decreased H3K4me1 levels, along with increased LSD1 levels, were detected on the TGIF2 promoter in the temporal cortex tissues of autistic mice.…”
Section: Discussionmentioning
confidence: 99%
“…One study has suggested that upregulation of specific histone methylation sites may be associated with disease in the rd1 mouse model of RP (Retinitis pigmentosa), with global inhibition shown to delay rod photoreceptor degeneration and improve visual function [ 19 ]. A recent study showed that the administration of a lysine demethylase 1 inhibitor in the rd10 model of RP (Retinitis pigmentosa) prevented rod death and preserved vision [ 20 ]. However, the role of histone methylation in the degeneration of cones specifically has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%